Effectiveness of Sports Massage in the Prevention and Rehabilitation of Muscle Injuries in Track and Field Jump Athletes: A Systematic Literature Review - Rudy Kharunia Harahap; Jiyad hawari; Frekdi Alosius Manik Frekdi Alosius Manik (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This systematic review aimed to evaluate the effectiveness of sports massage interventions in preventing and rehabilitating muscle injuries among track and field jump athletes, examining the impact on injury incidence, recovery time, performance outcomes, and functional restoration. Materials and methods: A comprehensive systematic literature review was conducted following PRISMA guidelines. Five electronic databases (PubMed, SPORTDiscus, Web of Science, Scopus, and CINAHL) were searched from inception to October 2024. Inclusion criteria encompassed randomized controlled trials, quasi-experimental studies, and cohort studies examining sports massage interventions in track and field jump athletes (long jump, triple jump, high jump, pole vault) aged 16 years and above. Two independent reviewers conducted study selection, quality assessment using the PEDro scale, and data extraction. Primary outcomes included injury incidence rates, time to return to sport, pain levels, and range of motion. Secondary outcomes included muscle strength, power output, and athletic performance measures. Results: Eighteen studies met the inclusion criteria, comprising 847 track and field jump athletes (mean age: 22.4 ± 3.8 years). Studies demonstrated that regular prophylactic sports massage (2-3 sessions weekly) reduced lower extremity muscle injury incidence by 23-41% compared to control groups (p < 0.05). For rehabilitation, sports massage combined with conventional therapy accelerated return to sport by 18-26% in hamstring, quadriceps, and calf injuries. Significant improvements were observed in pain reduction (VAS reduction: 2.8-4.2 points), range of motion (8-15% increase), and perceived recovery (p < 0.01). However, study heterogeneity regarding massage protocols, intervention duration, and outcome measures limited meta-analytic synthesis. Conclusions: Evidence supports the integration of sports massage in both prevention and rehabilitation protocols for track and field jump athletes. Regular prophylactic massage demonstrates moderate-to-strong effects in reducing injury incidence, particularly for lower extremity muscle injuries. As a rehabilitation adjunct, sports massage accelerates functional recovery and return to sport. Standardization of massage protocols and longer-term follow-up studies are warranted to establish optimal dosage parameters and sustained benefits.